The causality between economic growth, poverty, and stunting: empirical evidence from Indonesia - Dwi Darma Puspita Sari; Sukanto Sukanto; Taufiq Marwa; Abdul Bashir (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2020)
This study investigate the relationship between economic growth, poverty, and stunting in Indonesia. Observation during 2015-2017 in 34 regions in Indonesia. Using a spatial approach with Klassen's typology and applying the panel vector error correction model. The finding indicated that the priority handling of the problem of the high stunting prevalence focuses on the islands of Sulawesi, Maluku, Kalimantan, Nusa Tenggara, and Papua. Furthermore, addressing the problem of economic growth slows focuses on the Islands of Kalimantan and Sumatra. Meanwhile, the handling of high poverty levels focuses on the islands of Sulawesi, Sumatra, Nusa Tenggara, Maluku, and Papua. On the other side of this study, we get evidence of unidirectional causality flowing from poverty rates and the stunting prevalence toward economic growth in the long-run. The contribution of the stunting case is more dominant to have an impact on slowing economic growth. We also find evidence of unidirectional causality flowing from economic growth and stunting to poverty levels in the long-run, the contribution of economic growth is relatively more dominant with an impact on reducing poverty levels. While there is no evidence of causality flowing from economic growth and poverty to stunting, we have also found that poverty rates have a relatively high contribution to the increase in stunting cases in Indonesia.